Accelerated boundary element method for direct current interference of cathodic protections systems. (15th August 2022) - Kalovelonis, Dimitrios T.; Gortsas, Theodoros V.; Tsinopoulos, Stephanos V.; Polyzos, Demosthenes
Abstract: The use of cathodic protection (CP) is a widely used practice to mitigate the corrosion of metals. In certain circumstances, stray-current induced corrosion can occur on a structure when it interacts with the CP system of another nearby structure. Due to the locality of the phenomenon, stray-current induced corrosion is one of the most severe types of corrosion. The boundary element method (BEM) is ideal for solving CP problems. In the present work, two accelerated BEM formulations are presented to treat direct current interference problems. The first formulation is more efficient in solving small and medium scale problems, while the second one is more suitable for large scale problems. Furthermore, the stray current induced corrosion in an offshore platform due to its interaction with a nearby moored oil tanker is studied utilizing the above methodologies. The obtained numerical results are extensively discussed, and interesting conclusions are outlined. Highlights: The ACA/BEM methodology is extended for the first time for solving large scale DC interference problems. A new incremental methodology for solving DC interference problems is proposed. Solution of a large-scale DC interference problem in an offshore platform due to a nearby oil tanker, using two different numerical formulations.